Impact of Various Erosive Environments on the Durability of POM Fiber-Reinforced Ultra-High-Performance Concrete - Jingliang Dong; Yingliang Zong; Xiaopeng Shang; Xiaolei Chen; Zhen Tu; Ren Jiang; Zebing Zhu (Buildings)
To address the durability challenges faced by traditional concrete in marine environments, this study focuses on polyoxymethylene (POM) fiber-reinforced ultra-high-performance concrete (PFUHPC) and, for the first time, systematically investigates the inhibitory effects of POM fibers on microstructural degradation and mechanical performance deterioration of ultra-high-performance concrete under various erosive environments. The results indicated the following: (1) The mass loss rate and compressive strength degradation in PFUHPC under different erosive environments initially increased and then decreased, demonstrating that the inclusion of POM fibers delayed corrosion and significantly improved the durability and stability of the material’s performance. (2) Compared to the natural environment, after 180 days of immersion in different erosive environments (seawater immersion, wet–dry cycles in seawater, chloride salt immersion, sulfate salt immersion, and complex salt immersion), the compressive strength degradations were observed to be 4.8%, 9.7%, 6.8%, 11.7%, and 10.7%. (3) Microscopic analysis after 180 days revealed that the main corrosion products were gypsum, ettringite, and Friedel’s salt (calcium chloroaluminate). Under the environments of seawater immersion and cyclic wetting and drying, the low concentrations of chloride and sulfate ions resulted in fewer corrosion products and a denser matrix. The primary corrosion product under the chloride salt immersion was Friedel’s salt, which led to surface cracking and microporosity, while under the sulfate immersion, gypsum and ettringite were predominant, resulting in more porous and loosely bound hydration products and more severe corrosions.